EFFECT OF INORGANIC AND ORGANIC COPPER AND ZINC SUPPLEMENTATION ON HEMATOLOGICAL AND BLOOD BIOCHEMICAL PROFILE OF MALE KIDS (Indian Journal of Animal Production and Management, 2014)
A feeding trial with fifteen non-descript male kids (Capra hircus) 4-6 months of age was conducted at Animal Nutrition Shed, Indian Veterinary Research Institute, Izatnagar for a period of 120 days to determine the effects on supplementation of inorganic (sulphate) and organic (methionine) copper and zinc on haematological and blood biochemical parameters. All the kids were randomly subjected to three dietary treatments viz. T1 (Basal diet), T2 (Basal diet plus 7 ppm copper and 40 ppm zinc as sulphate) and T3 (Basal diet plus 7 ppm copper and 40 ppm zinc as methionine). The basal diet consisted of wheat straw and concentrates mixture (60:40) to meet the nutrients requirement of kids. Blood samples were collected at 0, 60 and 120 days of the experiment. Supplementation of 7 ppm copper and 40 ppm zinc from both sources over the basal diet had no effect on hematological (haemoglobin, packed cell volume) and blood biochemical profile (Glucose, total protein, albumin, globulin, albumin: globulin ratio, blood urea nitrogen, creatinine and cholesterol) of kids as the values were within the normal range in the study.
Keywords: Copper; Zinc; Methionine; Hemoglobin; Glucose; Total protein; Kids